2016
DOI: 10.1080/02640414.2016.1172725
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 4-week static stretching programme on the individual muscles comprising the hamstrings

Abstract: The aims of this study were to investigate the effects of a 4-week intervention of static stretching (SS) on muscle hardness of the semitendinosus (ST), semimembranosus (SM) and biceps femoris (BF) muscles. Shear elastic modulus was measured by using ultrasound shear wave elastography as the index of muscle hardness. Thirty healthy men (age 22.7 ± 2.2 years) volunteered for this study and were randomly assigned to the SS intervention group (n = 15) or the control group (n = 15). Participants in the SS interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 22 publications
3
58
1
Order By: Relevance
“…The pelvis was tilted anteriorly by placing a wedge between the pelvis and the bed. The knee joint was passively extended very slowly using the dynamometer manually by an examiner to prevent stretch reflex, starting from 90° flexion to the maximum angle that the participant could tolerate without pain or discomfort 16,17) . The change in the knee angle from 90° flexion was calculated, and the angle was defined as the final angle.…”
Section: Measurement Of Passive Stiffnessmentioning
confidence: 99%
“…The pelvis was tilted anteriorly by placing a wedge between the pelvis and the bed. The knee joint was passively extended very slowly using the dynamometer manually by an examiner to prevent stretch reflex, starting from 90° flexion to the maximum angle that the participant could tolerate without pain or discomfort 16,17) . The change in the knee angle from 90° flexion was calculated, and the angle was defined as the final angle.…”
Section: Measurement Of Passive Stiffnessmentioning
confidence: 99%
“…15 Interestingly, the magnitude of these changes may differ among the synergist muscles. 15 More precisely, a recent study has shown that a 4-week static stretching program induces a decrease in shear modulus in hamstring muscles, with a higher effect on the SM compared to the BF and ST. 10 However, the impact of chronic sport practice on individual muscle shear modulus has not been described. It is well known that most of sports activities involve bouncing and jumping with high-intensity stretch-shortening cycles (eg, soccer, basketball, athletic sprinting).…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, some studies have examined associations between muscle elasticity (i. e., shear modulus) and joint flexibility (e. g., ROM and joint stiffness) in plantar flexors [6,9,10]. Others have quantified the shear modulus of individual muscles of the hamstring [11][12][13][14][15], which is the most frequently strained muscle group and one of the most studied muscles in terms of joint flexibility [16][17][18]. However, little is known about whether and how muscle elasticity of the hamstring is associated with joint flexibility, especially joint stiffness.…”
Section: Introductionmentioning
confidence: 99%